# CHAPTER 3

POLYNOMIALS

DEFINITION:

A polynomial P(x) of degree n is an algebraic expression of the form

where n is a positive integer and an, an-1,…,a0 are constant, also called the coefficients and an 0 . an is called the leading coefficient and a0 is called the constant term.

Polynomial has its own special name.

where a, b, c, d and e are constants. The degree is given according to the highest power of the variable.

Examples of polynomials:

Polynomial Degree

1 3 2 0

are not polynomials.
. since they include terms with powers of x that are not positive integers.

also called polynomials of more than one variable respectively. However. in this chapter we will only discuss polynomials of one variable.
.

EXAMPLE 3.1
.The Algebraic Operations on Polynomials
Adding and subtracting polynomials The polynomials P(x) and Q(x) may be added or subtracted by collecting the same terms.

SOLUTION:
.

Multiplying polynomials
Note that every term in one polynomial is multiplied by every term in the other.2
.
EXAMPLE 3.

SOLUTION:
.

.Division of Polynomials
In the integer division
the divisor is 9. where remainder < divisor. The statement could be expressed as 32 = 3 x 9 + 5 = quotient x divisor + remainder. and the remainder is 5. the quotient is 3.

The quotient and remainder can be found by Long division Synthetic division
.
Similarly. polynomial can be expressed as P(x) = Q(x)D(x) + R(x).

7x2 + 2x + 4. divide P(x) by x – 3 SOLUTION:
.3 If P(x) = 3x3 .Long division of polynomials
EXAMPLE 3.

SOLUTION:
.

Where Q(x) = (3x2 + 2x + 8) and R(x) = 28. The remainder has a lower degree than divisor. D(x) denotes divisor and R(x) denotes remainder.7x2 + 2x + 4 is called dividend.
. Note that 3x3 . Where Q(x) denotes quotient.

Sol: Type equation here.Example:
Find the solution for the polynomial 𝑃 𝑥 = 3𝑥 3 − 1 that divide by 𝑥 + 1.
.

Ans 𝑄 𝑥 = 𝑥 2 − 2𝑥 + 4 and 𝑅 𝑥 = −9
.Quiz:
Find the degree of 𝑃 𝑥 = 𝑥 3 − 1.then determine the solution of P(𝑥) divide by 𝑥 + 2.

Synthetic division of polynomials
In synthetic division. the divisor. D(x) must be linear of the form x – h. Let P(x) = ax3 + bx2 + cx + d
.

Example 4
3
(+)
3
-7 9
2 6 8
4 24 28
(X)
3
2
.

Example 5
If 𝑃 𝑥 = 𝑥 4 + 4𝑥 2 + 𝑥 − 1. divide 𝑃(𝑥) by 𝑥 + 3
-3
(+)
1
0 -3
4 9 13
1 -39 -38
-1 114 113
(X)
1
-3
𝑃 𝑥 = 𝑥 3 − 3𝑥 2 + 13𝑥 − 38 𝑥 + 3 + 113
.

Remainder Theorem
When the polynomial P(x) is divided by a linear factor x – a. then the remainder is P(a)
.

Example 5
SOLUTION:
.

Example 6
SOLUTION:
.

Factor Theorem
If the remainder from dividing the polynomial P(x) by (x – a) is zero.
. then (x – a) must be a factor of the polynomial P(x).

Example 7
SOLUTION:
.

.

Example 8
SOLUTION:
.

. Every polynomial equation of degree n has exactly n roots. If P(a) = 0. Some of these roots may be repeated.Root and zeros of polynomial
Let P(x) be a polynomial of degree n. then x = a is a root of the polynomial equation. P(x) =0 x = a is also called a zero of the polynomial P(x) Note: In general. if x = a is a root of the polynomial equation P(x) = 0 then (x – a)is a factor of P(x).

Example 9
SOLUTION:
.

Example 10
SOLUTION:
.

.
The quotient Q(x) could be found by using long division or synthetic division.

.

Quadratic formula
Below is the formula for finding the roots of quadratic equation.
b b 4ac x 2a
2
. p(x)=ax2 + bx + c.

EXAMPLE
Find the roots of (a)
x2 x 6 0
(b)
(c)
x 4x 4 0
2
x 2x 8 0
2
.

Partial Fraction
.

We can usually apply this technique to algebraic fraction as a sum or difference of simpler algebraic fractions. The key to this process lies in the factorization of the denominator. We will consider three categories of denominator: Linear factor Quadratic factor Repeated factors: i) repeated linear factor ii) repeated quadratic factor
.

𝑄 𝑥 = 𝑎1 𝑥 + 𝑏1 𝑎2 𝑥 + 𝑏2 … (𝑎𝑟 𝑥 + 𝑏𝑟 ) can be expressed as 𝐴1 𝐴2 𝐴𝑟 + + ⋯+ 𝑎1 𝑥 + 𝑏1 𝑎2 𝑥 + 𝑏2 𝑎𝑟 𝑥 + 𝑏𝑟 where 𝐴1 . Example: 𝑥 + 3 𝐴 𝐵 = + (𝑥 − 2)(𝑥 + 4) 𝑥 − 2 𝑥 + 4
𝑃 𝑥 𝑄 𝑥
. 𝐴2 . … 𝐴𝑟 are constant.Linear factor in denominator
Let the fraction be
factors. If 𝑄(𝑥) is a product of linear
.

Solutions:
2𝑥 + 3 𝐴 𝐵 = + (𝑥 − 1)(𝑥 + 2) 𝑥 − 1 𝑥 + 2 2𝑥 + 3 𝐴(𝑥 + 2) 𝐵(𝑥 − 1) = + (𝑥 − 1)(𝑥 + 2) (𝑥 − 1)(𝑥 + 2) (𝑥 + 2)(𝑥 − 1) 2𝑥 + 3 𝐴 𝑥 + 2 + 𝐵(𝑥 − 1) = (𝑥 − 1)(𝑥 + 2) (𝑥 − 1)(𝑥 + 2) Since the denominator on both sides are equal it follows that the two numerators must be equivalent. 2𝑥 + 3 ≡ 𝐴 𝑥 + 2 + 𝐵 𝑥 − 1
.Example:
Write
2𝑥+3 (𝑥−1)(𝑥+2)
as partial fractions.

1 + 2 → 3𝐴 = 5 5 𝐴 = 3 1 𝐵 = 3 2𝑥 + 3 5 1 ∴ = + (𝑥 − 1)(𝑥 + 2) 3(𝑥 − 1) 3(𝑥 + 2)
[1] [2]
.Method 1: Comparing the coefficient of 𝑥 𝑛
2𝑥 + 3 ≡ 𝐴 𝑥 + 2 + 𝐵 𝑥 − 1 → 2𝑥 + 3 = 𝐴 + 𝐵 𝑥 + (2𝐴 − 𝐵) Comparing the coefficient of 𝑥 gives 𝑥: 𝐴 + 𝐵 = 2 Comparing the coefficient of constants gives. 𝐶𝑜𝑛𝑠𝑡𝑎𝑛𝑡𝑠: 2𝐴 − 𝐵 = 3 Solving the equation [1] and [2] simultaneously yields.

Choose some values of 𝑥 such that some of the constant can be get cancelled out.Method 2: Substitution of values 𝑥
This method involves substitution value of 𝑥 into the equivalent equation. 𝐴 or 𝐵 2𝑥 + 3 = 𝐴 𝑥 + 2 + 𝐵 𝑥 − 1 Let 𝑥 = −2 2 −2 + 3 = 𝐴 −2 + 2 + 𝐵 −2 − 1 −3𝐵 = −1 1 𝐵 = 3 Let 𝑥 = 1 2 1 + 3 = 𝐴 1 + 2 + 𝐵 1 − 1 3𝐴 = 5 5 𝐴 = 3 2𝑥 + 3 5 1 ∴ = + (𝑥 − 1)(𝑥 + 2) 3(𝑥 − 1) 3(𝑥 + 2)
.

This algebraic fraction could
𝑥+2
be rewritten as 3𝑥 + 5 𝐴 𝐵 = + 2 𝑥 + 2 𝑥 + 2 𝑥 + 2
2
.Repeated linear factor in denominator
Some algebraic function have denominator that repeated 3𝑥+5 factors. For example 2 .

9 = 𝐴 1 + 2
+ 𝐵 1 − 1 1 + 2 + 𝐶 1 − 1 9𝐴 = 9 → 𝐴 = 1
Let 𝑥 = 0. (any) 9 = 4𝐴 − 2𝐵 − 𝐶 2𝐵 = 4𝐴 − 𝐶 − 9 2𝐵 = 4 + 3 − 9 𝐵 = −1 9 1 1 3 ∴ = − − 𝑥 − 1 𝑥 + 2 2 𝑥 − 1 𝑥 + 2 𝑥 + 2
2
. 9 𝐴 𝐵 𝐶 = + + 𝑥 − 1 𝑥 + 2 2 𝑥 − 1 𝑥 + 2 𝑥 + 2 2 9 𝐴 𝑥 + 2 2 + 𝐵 𝑥 − 1 𝑥 + 2 + 𝐶(𝑥 − 1) = 𝑥 − 1 𝑥 + 2 2 (𝑥 − 1) 𝑥 + 2 2 ∴ 9 = 𝐴 𝑥 + 2 2 + 𝐵 𝑥 − 1 𝑥 + 2 + 𝐶(𝑥 − 1) 9 = 𝐴 −2 + 2
2
Solution:
Let 𝑥 = −2.
+ 𝐵 −2 − 1 −2 + 2 + 𝐶 −2 − 1 −3𝐶 = 9 → 𝐶 = −3
2
Let 𝑥 = 1.Example:
Express
9 𝑥−1 𝑥+2 2
in partial fractions.

Quadratic factors in the denominator
Some algebraic fractions have denominator that contain a quadratic factor that cannot factorized. such as 5 𝐴𝑥 + 𝐵 = 2 2+3 𝑥 𝑥 + 3 Example: Express the following as partial fractions: 4𝑥 (𝑥 + 1)(3 + 𝑥 2 )
.

Solution:
4𝑥 𝐴 𝐵𝑥 + 𝐶 = + 2 2) (𝑥 + 1)(3 + 𝑥 𝑥 + 1 𝑥 + 3 4𝑥 𝐴 𝑥 2 + 3 + 𝐵𝑥 + 𝐶 𝑥 + 1 = 2) (𝑥 + 1)(3 + 𝑥 (𝑥 + 1)(𝑥 2 + 3) Equaling the numerators. 2 𝐴 = − . 𝑥 and constant. 𝐶 = 2 3 4𝑥 2 2𝑥 + 2 ∴ =− + 2 2) (𝑥 + 1)(3 + 𝑥 3(𝑥 + 1) 𝑥 + 3
. 𝐵 = 2. 4𝑥 = 𝐴 𝑥 2 + 3 + 𝐵𝑥 + 𝐶 𝑥 + 1 4𝑥 = 3𝐴𝑥 2 + 3𝐴 + 𝐵𝑥 2 + 𝐵𝑥 + 𝐶𝑥 + 𝐶 4𝑥 = 3𝐴 + 𝐵 𝑥 2 + 𝐵 + 𝐶 𝑥 + (3𝐴 + 𝐶) By comparing the coefficient of 𝑥 2 .

…. 𝐴𝑟 . 𝐴2 . 𝐵2 . . … .Repeated quadratics factors in denominator
The repeated quadratic factors in denominator can wrote as: 𝐴1 𝑥 + 𝐵1 𝐴2 𝑥 + 𝐵2 𝐴𝑟 𝑥 + 𝐵𝑟 . 𝐵𝑟 are constants. 2 2 + 𝑏𝑥 + 𝑐 𝑎𝑥 2 + 𝑏𝑥 + 𝑐 𝑎𝑥 𝑎𝑥 + 𝑏𝑥 + 𝑐 And 𝐴1 . 𝐵1 .
.

𝑥 and constant. 𝐵 = −1. 𝐶 = 0. 1 − 𝑥 2 = 𝐴𝑥 + 𝐵 1 + 𝑥 2 + 𝐶𝑥 + 𝐷 1 − 𝑥 2 = 𝐴𝑥 + 𝐴𝑥 3 + 𝐵 + 𝐵𝑥 2 + 𝐶𝑥 + 𝐷 1 − 𝑥 2 = 𝐴𝑥 3 + 𝐵𝑥 2 + 𝐴 + 𝐶 𝑥 + (𝐵 + 𝐷) Comparing the coefficient of 𝑥 2 . 𝐴 = 0. 1 − 𝑥 2 1 + 𝑥 2 2 Solutions: 1 − 𝑥 2 𝐴𝑥 + 𝐵 𝐶𝑥 + 𝐷 = + 1 + 𝑥 2 2 (1 + 𝑥 2 ) 1 + 𝑥 2 2 1 − 𝑥 2 𝐴𝑥 + 𝐵 1 + 𝑥 2 + (𝐶𝑥 + 𝐷) = 1 + 𝑥 2 2 (1 + 𝑥 2 ) Equating the numerators.Example:
Express the following as partial fractions. 𝐷 = 2 1 − 𝑥 2 1 2 =− + 1 + 𝑥 2 2 (1 + 𝑥 2 ) 1 + 𝑥 2 2
.

The End
Last Edit: 31/10/2011
.